Differentiated learning: Implementation and challenges to student learning outcomes - Elsa Puspasari; Oki Anggraeni (Soedirman Economics Education Journal, 2026)
This study aims to examine the effectiveness of differentiated learning on students' learning outcomes and identify the challenges faced in its implementation. The method used is quantitative experiment with pretest-posttest control group design. The research sample consisted of two classes at the junior secondary education level that were randomly selected. The experimental class was treated using differentiated learning with differentiated learning with problem based learning model, while the control class used conventional learning model. The research instruments were learning outcome tests and implementation challenge questionnaires filled out by teachers. Data analysis using t-test showed that there was a significant difference between student learning outcomes in the experimental and control classes (p < 0.05), indicating that differentiated learning is effective in improving student learning outcomes. However, questionnaire data shows that teachers face a number of challenges, such as time constraints, lack of training, and difficulties in grouping students based on learning needs. The findings provide important implications for education policy and practice in supporting the optimal implementation of differentiated learning.